Perceptions of spiritual nursing care for patients recovered from Covid-19. A phenomenological exploration - Conde Sarango, Ana María (2023)
Objective: To explore the spiritual care provided by the nursing professionals in the emergency service of the Hospital General Machala from the perspective of patients infected by Covid-19. Material and Methods: Qualitative, phenomenological research. An intentional sample was used to select 8 patients recovered from Covid-19. Data collection was obtained through in-depth semi-structured interviews. Transcription was done manually as soon as possible. For data analysis, the method created by Colaizzi was used. Results: Four main categories were obtained: 1) Factors of spiritual suffering in patients with Covid-19; 2) Spiritual needs of Covid-19 patients; 3) Satisfaction of the spiritual care provided by nursing; and, 4) Main barriers perceived to spiritual care. Conclusion: It was shown that patients recovered from Covid-19 perceived both positive and negative experiences related to spiritual care, this being a key component to assess spiritual needs. We suggest using the findings found in this study for future research to develop a structured program supervised by experts to improve spiritual care in health care.